Escala de Mitos do Amor Romântico (EMAR): Portuguese Version of the Scale of Myths of Romantic Love (SMRL) - Jaume Grané-Morcillo; Susana Costa-Ramalho; Carles Pérez-Testor; Berta Vall (Social Sciences)
Background: Violence legitimization has been associated with the myths of romantic love. In the Portuguese context, there are no available standardized tools to assess it. This study aimed to develop the adaptation and validation of the Portuguese version of the Scale of Myths of Romantic Love (SMRL) in youth and emerging adults. Also, the acceptance of myths of romantic love was described. Methods: The sample comprised 165 individuals (83% female) aged from 18 to 30 (M = 23.01; SD = 3.33). Results: Confirmatory factor analysis supported the two-factor correlated structure found in the original validation: Idealized Love (IL) and Distorted Love (DL). The selected nested model obtained acceptable good-of-fit indices. Reliability analysis indicated acceptable internal consistency (α = 0.728; ω = 0.711) and the item-factor correlations were strong. Gender differences in the endorsement of romantic myths were found. Males obtained significantly greater acceptance of need for a couple and ambivalence myths. Females significantly endorsed the half orange myth. Conclusions: Our findings supported the two-factor related structure of the SMRL Portuguese version. Gender-based differences in romantic beliefs and their potential link to violence legitimization, gender stereotypes, and love perception are highlighted as in need of further studies. This research provides evidence regarding the psychometric properties of the Escala de Mitos do Amor Romântico (EMAR).